Impact of a four-domain intrinsic capacity measure on falls: findings from the EPOSA study - Ceolin, Chiara; Siviero, Paola; Limongi, Federica; Noale, Marianna; Sergi, Giuseppe; Maggi, Stefania; , the EPOSA Research Group (Frontiers in Aging, 2025)
ObjectiveLow Intrinsic Capacity (IC) has been associated with adverse health outcomes in older adults, including falls. This study examines a four-domain measure of IC (cognition, psychological, locomotion, vitality) and its relationship with fall risk in a large European cohort.MethodsData were from the European Project on Osteoarthritis (EPOSA) study. IC, operationalized using four domains (cognition, psychological, locomotion, vitality), was assessed on 2,597 adults (65–85 years) of six countries, with follow-up data at 12–18 months. Logistic regression models were used to evaluate its association with falls after the baseline, adjusting for sociodemographic, socioeconomic, and health factors, including osteoarthritis.ResultsThe median IC score was 6 (IQR: 5–7) and varied by country. Italy, Spain and the United Kingdom had the lowest scores, particularly in the locomotion, psychological and cognitive domains. Of the 2,127 participants who completed the follow-up, 26.8% reported falls. Multivariable analysis revealed significant associations between falls and IC, joint replacement, clinical osteoarthritis, analgesic/anti-inflammatory medication use and tobacco consumption, as well as a borderline association with cardiovascular disease. Individuals with a low IC score (<5) had a 1.57 times greater risk of falling.DiscussionLow IC, based on four domains, predicts falls in older adults. Identifying individuals with low IC can aids targeted interventions to reduce risk and health burdens. Prevention programs should integrate physical, cognitive, and psychological support while considering clinical and demographic interactions. These findings highlight the value of multidomain IC assessment as a tool for promoting healthy aging.